Knowledge and attitudes towards influenza and influenza vaccination among pregnant women in Kenya. Issue 43 (7th October 2020) - Otieno, Nancy A.; Nyawanda, Bryan; Otiato, Fredrick; Adero, Maxwel; Wairimu, Winnie N.; Atito, Raphael; Wilson, Andrew D.; Gonzalez-Casanova, Ines; Malik, Fauzia A.; Verani, Jennifer R.; Widdowson, Marc-Alain; Omer, Saad B.; et al.
Highlights: Willingness to be vaccinated against influenza while pregnant was high. Willingness to vaccinate was higher among pregnant women who knew about influenza. Government recommendation for the vaccine may lead to higher rates of acceptance. Improving disease knowledge and mitigating safety concerns may improve acceptance. Hesitant mothers should be educated on benefits of the vaccine during pregnancy. Abstract: Background: Influenza vaccination during pregnancy benefits mothers and children. Kenya and other low- and middle-income countries have no official influenza vaccination policies to date but are moving towards issuing such policies. Understanding determinants of influenza vaccine uptake during pregnancy in these settings is important to inform policy decisions and vaccination rollout. Methods: We interviewed a convenience sample of women at antenatal care facilities in four counties (Nairobi, Mombasa, Marsabit, Siaya) in Kenya. We described knowledge and attitudes regarding influenza vaccination and assessed factors associated with willingness to receive influenza vaccine. Results: We enrolled 507 pregnant women, median age was 26 years (range 15–43). Almost half (n = 240) had primary or no education. Overall, 369 (72.8%) women had heard of influenza. Among those, 288 (78.1%) believed that a pregnant woman would be protected if vaccinated, 252 (68.3%) thought it was safe to receive a vaccine while pregnant, and 223 (60.4%) believed a baby would be protected if mother was vaccinated. If given opportunity, 309 (83.7%) pregnant women were willing to receive the vaccine. Factors associated with willingness to receive influenza vaccine were mothers' belief in protective effect (OR 3.87; 95% CI 1.56, 9.59) and safety (OR 5.32; 95% CI 2.35, 12.01) of influenza vaccines during pregnancy. Conclusion: Approximately one third of pregnant women interviewed had never heard of influenza. Willingness to receive influenza vaccine was high among women who had heard about influenza. If the Kenyan government recommends influenza vaccine for pregnant women, mitigation of safety concerns and education on the benefits of vaccination could be the most effective strategies to improve vaccine acceptance.